KESETARAAN DAN KEADILAN GENDER DALAM ADAT MINANGKABAU - Rahima Zakia (Universitas Islam Negeri Imam Bonjol Padang, 2011)
Adat Minangkabau has the values of equality and gender justice. Men and women based on the status and function are given rights, obligations and responsibilities in proportion. Fairness and equality of cover sako and pusako heritage, as well as participation in decision making. Women as Bundo Kanduang has domestik and public roles. The man is like the proverbial